Validity of internal structure of the Competitive State Anxiety Inventory in a Brazilian sample - Daniel Bartholomeu; José Maria Montiel; Afonso Antonio Machado (Universidade Estadual Paulista (UNESP), 2014)
This study investigated internal structure validity of the CSAI-2. The sample comprised 172 in Brazilian athletes, both sexes and ages ranging from 14 to 58 years. The athletes attended to the following sports: basketball, soccer, handball, volleyball and jiu-jitsu. The CSAI-2 was collectively applied before training. Initially a confirmatory factor analysis was done, but the data did not fit the model. Then, an exploratory factor analysis was conducted and, although the parallel analysis pointed out the adequacy of a two factor model, the three factor model was the one that best explained the test's theory, with some items excluded from the analysis. The factor's precision was taken by means of Cronbach's alpha and item-total correlation index and showed good results.